SIX LESSONS FROM HAITI: THE NEED FOR COOPERATION DEVELOPMENT - Tania García Lorenzo; Milagros Martínez Reinosa; Stephen Wilkinson (International Journal of Cuban Studies, 2010)
One of the defining events of 2010 took place at its start. On 12 January, the long suffering of the Haitian people took on a grave new dimension, one that will last for years. For a few days, news of the tragedy filled the mass media and the eyes and thoughts of men and women across the world, who from their homes felt the anguish of that population that has more than paid for the audacity of wanting to be independent and free from slavery. In one of the news stories, a mother asked, 'What has Haiti done to deserve this?' The reading that follows: on the event itself, its impact and the manner and magnitude of the response is performed with a gaze that starts from Haiti, but spreads to the Caribbean Basin, the hemisphere and the world. These notes reflect on the lessons that Haiti offers, what it shows and proves, because Haiti is now a mirror in which we must look not only at the Caribbean, but at all the underdeveloped world.